2018
DOI: 10.1371/journal.pone.0190914
|View full text |Cite
|
Sign up to set email alerts
|

Australian shellfish ecosystems: Past distribution, current status and future direction

Abstract: We review the status of marine shellfish ecosystems formed primarily by bivalves in Australia, including: identifying ecosystem-forming species, assessing their historical and current extent, causes for decline and past and present management. Fourteen species of bivalves were identified as developing complex, three-dimensional reef or bed ecosystems in intertidal and subtidal areas across tropical, subtropical and temperate Australia. A dramatic decline in the extent and condition of Australia’s two most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 53 publications
0
101
0
Order By: Relevance
“…The global Shellfish Reefs at Risk assessment (Beck et al, ; Beck et al, ) revealed steep and widespread declines in native populations of ecosystem‐forming bivalves such as oysters and mussels (herein “shellfish reefs”), which was confirmed by subsequent and more detailed national and regional studies (e.g., Alleway & Connell, ; Ford & Hamer, ; Gillies et al, , ; Pogoda, ). Acknowledgment of the loss of these ecosystems coupled with growing recognition of the valuable functional role shellfish reefs perform in coastal systems, including water filtration, coastal protection, and fish production (e.g., Coen et al, ; Grabowski et al, ), has led to widespread interest in their restoration and protection (Baggett et al, , ; Gillies et al, ; Gillies, Crawford, & Hancock, ; Theuerkauf & Lipcius, ; zu Ermgassen et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…The global Shellfish Reefs at Risk assessment (Beck et al, ; Beck et al, ) revealed steep and widespread declines in native populations of ecosystem‐forming bivalves such as oysters and mussels (herein “shellfish reefs”), which was confirmed by subsequent and more detailed national and regional studies (e.g., Alleway & Connell, ; Ford & Hamer, ; Gillies et al, , ; Pogoda, ). Acknowledgment of the loss of these ecosystems coupled with growing recognition of the valuable functional role shellfish reefs perform in coastal systems, including water filtration, coastal protection, and fish production (e.g., Coen et al, ; Grabowski et al, ), has led to widespread interest in their restoration and protection (Baggett et al, , ; Gillies et al, ; Gillies, Crawford, & Hancock, ; Theuerkauf & Lipcius, ; zu Ermgassen et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…Individual reef patches could measure over 100,000 m −2 (10 ha), with numerous reef patches combining to form extensive reef systems (Ogburn et al ). Subtidal S. glomerata reefs were found at depths of up to 8 m (Gillies et al ), with historical descriptions of reefs so abundant with oysters that a fisher could “[tie] his boat to a stake, then [commence] to dredge for six months” (Lergessner ). Today, no subtidal reefs and only six intertidal S. glomerata reef systems remain from at least 60 known historical locations; an estimated 92% of large S. glomerata reefs have been lost (Gillies et al ).…”
Section: Introductionmentioning
confidence: 99%
“…By the end of the 19th century, oyster reefs were so degraded that wild fisheries were largely abandoned, leading to increased adoption of S. glomerata aquaculture, NSW's oldest aquaculture industry (since 1870, Nell ). Despite a significant decline in wild commercial harvest of S. glomerata by the mid‐1900s, little natural recovery has occurred (Gillies et al ). Combined with the shift from a shell to sedimentary habitat, oyster disease, invasive mud worm, pollution, and increased sediment loads from catchment disturbances have all contributed to the lack of S. glomerata reef recovery (Kirby ; Ogburn et al ; Beck et al ; Diggles ).…”
Section: Introductionmentioning
confidence: 99%
“…Intertidal ecosystem engineers (e.g., bivalves, barnacles, cordgrass, macroalgae: Seed, ; Bruno & Kennedy, ; Burnaford, ; Cartwright & Williams, ) can provide cool microclimates and, unlike substrate topography (i.e., crevices, rock pools), can respond to the changing environment (Duarte, Losada, Hendriks, Mazarrasa, & Marbà, ). Gregariously settling bivalves such as oysters and mussels, for example, can form dense aggregations of various topographies on soft and hard coastal substrata, producing habitats ranging from two‐dimensional beds on hard substrata to three‐dimensional oyster reefs (Gillies et al, ; Figure ). Consequently, on mid‐intertidal substrata in many parts of the world, these habitat‐forming bivalves are often dominant space occupants, in some instances approaching 100% cover (Bahr & Lanier, ; McAfee, Cole, & Bishop, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gregariously settling bivalves such as oysters and mussels, for example, can form dense aggregations of various topographies on soft and hard coastal substrata, producing habitats ranging from two-dimensional beds on hard substrata to three-dimensional oyster reefs (Gillies et al, 2018; Figure 1). Consequently, on mid-intertidal substrata in many parts of the world, these habitat-forming bivalves are often dominant space occupants, in some F I G U R E 1 Habitat formed by intertidal rock oysters (genus Saccostrea) varies from (a, b) flat, horizontal forms that encrust the rocky substrata to (c, d) elevated, protruding forms where the oysters grow vertically…”
Section: Introductionmentioning
confidence: 99%